Characterisation of Conciato Romano: one of the oldest Italian cheeses. (September 2021) - Blaiotta, Giuseppe; Marrone, Raffaele; Aponte, Maria; Peruzy, Maria Francesca; Smaldone, Giorgio; Vollano, Lucia; Murru, Nicoletta
Abstract: Conciato Romano is believed to be the oldest Italian ewe cheese; it is manufactured according to an unusual technology, ending with a long ripening in earthenware jars. Cheese was monitored during production and ripening in two different seasons: winter and spring. According to the data obtained, the ripening in jars prevents lipid oxidation, and ensures the safety of the product. Coagulase-positive staphylococci, Salmonella and Listeria spp. were never retrieved, while Enterobacteriaceae and Escherichia coli disappeared during the ripening, likely due to the antimicrobial activity of the tanning of the cheeses. Mesophilic lactic acid bacteria dominated the entire production process, with Lactiplantibacillus plantarum subsp . plantarum and enterococci accounting for about 26% and 30%, respectively, of the total cultures isolated (203). Total monounsaturated fatty acids and ω-3 and ω-6 polyunsaturated fatty acids were higher in cheeses produced during spring, while the atherogenic index was significantly lower. Outcomes of texture analysis confirmed seasonal differences, stressing the role of the animals' feeding regimen.